The Relationship Between Surgical Safety Checklist Implementation Compliance with Post Postoperative Adverse Events (PAE) - Tatali, Febriyanto; Suwanti; Sukmawijaya, Dody; Rijaldi, Aldi (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
The Unexpected events (Postoperative Untoward Events/PUE) occurring in the operating room remain one of the most pressing patient safety issues in modern surgical practice. These events, ranging from surgical site infections and wrong-site surgery to retained instruments and anesthesia-related complications, contribute substantially to increased morbidity, prolonged hospital stays, and elevated healthcare costs. The Surgical Safety Checklist (SSC), introduced by the World Health Organization (WHO) in 2008, was developed as a structured, low-cost intervention consisting of three critical phases—sign in, time out, and sign out—each designed to verify essential safety parameters before, during, and after surgical procedures. This study aims to analyse the relationship between the level of compliance with SSC implementation and the incidence of unexpected postoperative events (PAE/PUE), as well as to identify the primary factors that hinder optimal checklist adherence among surgical teams. Methods: This study employed an analytical observational design using a cross-sectional approach. The study population comprised surgical cases performed at the Central Surgical Installation of General Hospital (X). A total of 120 surgical cases occurring between January and June 2024 were selected as the sample using a consecutive sampling technique, in which every case meeting the inclusion criteria during the study period was enrolled sequentially until the required sample size was achieved. SSC compliance was assessed through direct observation and documentation review across the three checklist phases, while postoperative adverse events were identified from medical records and clinical follow-up within 48 hours after surgery. Data were analysed using the chi-square test. Results of this study were the overall SSC compliance rate across all surgical phases was 68.3%. Compliance varied notably by phase, with the time out phase demonstrating the highest adherence (82.5%), while the sign out phase showed the lowest compliance (57.5%), suggesting that post-procedural verification steps are frequently overlooked or rushed. Statistical analysis revealed a significant relationship between overall SSC compliance and the incidence of PUE (p = 0.001; OR = 4.82; 95% CI: 2.14–10.86), indicating that surgical teams with low compliance were nearly five times more likely to experience postoperative adverse events compared to those with high compliance. Conclusions of this study was compliance with SSC implementation is significantly correlated with a reduction in the incidence of postoperative PUE. These findings underscore that the checklist's effectiveness lies not in its mere existence but in rigorous, consistent execution across all three phases. Strengthening institutional safety culture, providing continuing education, and addressing hierarchical barriers within surgical teams are essential interventions to improve SSC adherence and enhance patient safety outcomes.